Preparation of highly (001)‐oriented photoactive tungsten diselenide (WSe2) films by an amorphous solid–liquid‐crystalline solid (aSLcS) rapid‐crystallization process. Issue 9 (16th May 2014) - Bozheyev, Farabi; Friedrich, Dennis; Nie, Man; Rengachari, Mythili; Ellmer, Klaus
<x xml:space="preserve">Abstract</x> Highly (001)‐textured tungsten diselenide WSe2 thin films have been prepared by a two‐step process on quartz glass and TiN metallic back contacts, respectively. At first, X‐ray amorphous, selenium‐rich WSe2+x films were deposited by reactive magnetron sputtering at room temperature onto a thin metal promoter film (Ni or Pd) and afterwards annealed in an H2Se/Ar atmosphere. X‐ray diffraction and scanning electron microscopy show that highly (001)‐oriented WSe2 films can be grown, which is caused by the formation of liquid promoter‐metal selenide droplets which dissolve tungsten or tungsten selenide at temperatures, higher than the eutectic temperature in the promoter metal–selenium system, followed by oversaturation and eventually crystallization of WSe2 platelets. Time‐resolved microwave conductivity measurements show that the films are photoactive. The sum of the carrier mobilities of the best films µe + µh is in the range of 1–7 cm2 V−1 s−1.